Determinants of Grand Multiparity (Journal of Fatima Jinnah Medical University, 2018)
OBJECTIVES: To determine the reasons for grand multiparitySTUDY DESIGN: Descriptive studySETTING: Department of Obstetrics and Gynecology, Sir Ganga Ram Hospital Lahore from July to December 2011.METHODOLOGY: 100 patients who presented in their fifth pregnancy and onwards after twentieth week of gestation were included. Data was collected from selected cases using proforma questionnaire. Statistical analysis was done using software SPSS version 14.RESULTS: Results showed 96% were grand multipara and 6% were great grand multipara. Only 12% women had planned conception. Mean age was 31.40 + 4.32 years and mean duration of marriage was 12.71 + 3.8 years. In 33.3% great grand multipara duration of marriage was 20 years or more. Results showed that 55% wives and 38% husbands were illiterate and 94% living below poverty line. Causative factors identified were teen age marriage in 66%, husband pressure for male child in 43% and for female child in 7%, mother in law pressure for male child 21%, bad obstetric history in 6%, second marriage of female partner in 2%, religious factor in 12% cases. Study show 89% women have some Knowledge of contraceptive methods and only 39% ever practiced any of the contraceptive methods. Other factors were contraceptive failure in 10%, inaccessibility to family planning services in 5% and 11% had one or more induced miscarriage.CONCLUSION: Teen age marriage, social pressure to have male child and non-usage of effective contraceptive methods are the major factors responsible for grand multiparity. Illiteracy and poverty are other contributing factors.
Keywords: grandmultiparity, great grandmultiparity, multiparity